2012
DOI: 10.1103/physrevb.86.224421
|View full text |Cite
|
Sign up to set email alerts
|

Ho and Fe magnetic ordering in multiferroic HoFe3(BO3)4

Abstract: Resonant and nonresonant x-ray scattering studies on HoFe 3 (BO 3 ) 4 reveal competing magnetic ordering of Ho and Fe moments. Temperature and x-ray polarization dependent measurements employed at the Ho L 3 edge directly reveal a spiral spin order of the induced Ho moments in the ab plane propagating along the c axis, a screw-type magnetic structure. At about 22.5 K the Fe spins are observed to rotate within the basal plane inducing spontaneous electric polarization, P. Components of P in the basal plane and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The investigation of weak non-resonant magnetic reflections in SmFeAsO shows that very weak signals can be measured reliably 35 . Full polarization analysis, performed at the Ho L 3 -edge of HoFe 3 (BO 3 ) 4 could be used to show the spiral magnetic order along the c-axis 36 . From azimuthal scans at the Ir L 3 -edge of Sr 2 IrO 4 , the ordering of the Ir moments in the basal plane could be determined and be related to the ordering in Ba 2 IrO 4 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of weak non-resonant magnetic reflections in SmFeAsO shows that very weak signals can be measured reliably 35 . Full polarization analysis, performed at the Ho L 3 -edge of HoFe 3 (BO 3 ) 4 could be used to show the spiral magnetic order along the c-axis 36 . From azimuthal scans at the Ir L 3 -edge of Sr 2 IrO 4 , the ordering of the Ir moments in the basal plane could be determined and be related to the ordering in Ba 2 IrO 4 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Подходящими R-ионами для синтеза и исследования замещенного ферробората с конкурирующими обменными взаимодействиями являются ионы Ho 3+ и Nd 3+ . Магнитные моменты железа в HoFe 3 (BO 3 ) 4 антиферромагнитно упорядочиваются при T N ≈ 38−39 K и при понижении до температуры T SR ≈ 4.7−5 K лежат в базисной плоскости ab, также как и магнитные моменты ионов Ho 3+ [3,8,9]. При T SR ≈ 4.7−5 K происходит спонтанный спин-переориентационный переход, в результате которого магнитные моменты Hoи Fe-подсистем становятся ориентированными вдоль оси c. В NdFe 3 (BO 3 ) 4 при T < T N ≈ 31 K все магнитные моменты лежат в базисной плоскости ab [10,4].…”
Section: Introductionunclassified
“…In addition, there are literature reports of x-ray measurements of holmium ferroborate. 12 The authors found the occurrence of an incommensurate magnetic structure below T ¼ 22.5 K, which is below the temperature of magnetic ordering, 38 K. This structure disappears at a temperature of 4.8 K when a spin-reorientation transition occurs into the "easy-axis" phase.…”
mentioning
confidence: 98%
“…12 Therefore the broadening of the lines of the AFMR spectrum can be explained by different projections of the magnetic moments of the Fe 3þ ions along the Hjjx direction. We know that in Ref.…”
mentioning
confidence: 99%